Building research capacity in an under‐represented group: The STAARS program experience. Issue 4 (12th July 2022) - Schreiber, Kelsey L.; Barrett, Christopher B.; Bageant, Elizabeth R.; Shimeles, Abebe; Upton, Joanna B.; DiGiovanni, Maria
Abstract: For decades, the lack of high‐quality empirical economic research on the state of Africa's agriculture and rural economies has been an important factor impeding the formulation of evidence‐based policy on the continent. The Structural Transformation of African Agriculture and Rural Spaces program aims to build a critical mass of early career African scholars and policy research through an emphasis on mentorship and professional development to help remedy that deficiency. This paper explains the motivations, origins, and outcomes to date of the program, and offers lessons learned for others wishing to create research capacity development opportunities for under‐represented groups.